2020
DOI: 10.1016/j.jsames.2020.102742
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and isotopic features of Li-rich brines from the Salar de Olaroz, Central Andes of NW Argentina

Abstract: The lithium-rich brines of the Salar de Olaroz in the Central Andes of NW Argentina are considered to be of great economic and strategic interest. This study focused on the fluid source(s) and geochemical processes governing the chemical and isotopic characteristics of the surficial waters of Olaroz (residual brines, ephemeral lakes, rivers and tributary streams), aiming to define the mechanisms leading to such a huge Li reservoir. The chemistry of the Rosario River, which is one of the main sources of recharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…A correspondence between Li grades and salar sizes may reflect the importance of basin scale processes such as rock weathering, isolation, evaporation, and time (López Steinmetz et al, 2020b). This would be consistent with the model proposed for the formation of the Atacama's and Olaroz's brines, which took place in a near-surface setting through geochemical processes such as low-temperature weathering, evaporation, formation of transition-zone brines, and ultimately crystallization of halite to increase the concentration of Li in the brines (Munk et al, 2018;Franco et al, 2020). As already mentioned in section 5.1., other studies have reported Li isotopic data showing that volcanic and Paleozoic basement rocks represent the primary source for Li in the Andean plateau (Egenhoff and Lucassen, 2003;Peralta Arnold et al, 2017;García et al, 2019;Meixner et al, 2019).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 80%
“…A correspondence between Li grades and salar sizes may reflect the importance of basin scale processes such as rock weathering, isolation, evaporation, and time (López Steinmetz et al, 2020b). This would be consistent with the model proposed for the formation of the Atacama's and Olaroz's brines, which took place in a near-surface setting through geochemical processes such as low-temperature weathering, evaporation, formation of transition-zone brines, and ultimately crystallization of halite to increase the concentration of Li in the brines (Munk et al, 2018;Franco et al, 2020). As already mentioned in section 5.1., other studies have reported Li isotopic data showing that volcanic and Paleozoic basement rocks represent the primary source for Li in the Andean plateau (Egenhoff and Lucassen, 2003;Peralta Arnold et al, 2017;García et al, 2019;Meixner et al, 2019).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 80%